Hydrophobins: multitask proteins - Rojas-Osnaya, Jesús; Quintana-Quirino, Mariana; Espinosa-Valencia, Alejandra; Bravo, Ana Luisa; Nájera, Hugo (Frontiers in Physics, 2024)
Hydrophobins are small amphiphilic extracellular proteins produced by filamentous fungi; they are surface active proteins, and their functions are mainly related to their ability to self-assemble into amphipathic monolayers at hydrophobic-hydrophilic interfaces. Depending on their hydropathy patterns and purification requirements, they are classified into class I and class II; both present eight conserved cysteines throughout their sequence, forming four disulfide bridges, which generate four loops that give stability to the protein in its monomeric and folded form. Class I hydrophobin loops are more extended than class II hydrophobin loops, resulting in differences in assembly to divergent surfaces, additionally accompanied by conformational changes in the protein structure. In the monomer hydrophobin glycosylated form, hydrophobins are rich in beta-sheet structure, while being assembled at the water-air interface increases the content of beta-sheet in their structure and is at the interface with water and a hydrophobic solid such as Teflon also induces the formation of an alpha-helix structure. The monolayers generated by class I are stable structures called fibrils or rodlets, and class II only produces aggregates. Class I presents a glycosylated chain in its sequence; this causes the formation of an alpha-helix structure, promoting ordered assemblies, which entails their stability and high insolubility. Fibrils could be dissociated with trifluoroacetic acid and formic acid, which unfolds the protein, while 60% ethanol and 2% sodium dodecyl sulfate solutions dissociate class II aggregates.